POTENSI SUMBER RISIKO PADA PRODUKSI KECAP CAP JAGO (Studi Kasus PT Ahon Janata Haurda, Kecamatan Parigi, Kabupaten Pangandaran) - Bajrah, Muhammad Rian; Trimo, Lucyana; Supyandi, Dika; Saidah, Zumi (Universitas Galuh, 2023)
Productivity of Cap Jago soy sauce at PT Ahon Janata Haurda is still low and spread in Pangandaran Regency and its surroundings. In addition, requests are not always fulfilled on time. Various risks that exist in production activities are the cause of the problem. The purpose of this study is to find a risk agent has the greatest potential for soy sauce production at PT Ahon Janata Haurda. This research is qualitative with a case study research technique. The analytical method used is descriptive analysis and HOR (House Of Risk). The results showed that there were 6 out of 13 risk agent that most determines the risk event namely: high rainfall, the quality of varied raw materials, the weather is uncertain, long droughts, competition for raw materials, the dosage of raw materials is not appropriate. Risk agent has an impact of 79.25% of all existing risk sources.